The Interrelationship of Urban Economic and Cultural Development: the Case of Greek Museums - Alex Deffner; Theodoros Metaxas (European Regional Science Association (ERSA), 2003)
The purpose of the paper is the pinpointing of the role and importance of museums in the cultural and economic development of cities. The starting point is a critical analysis of the international, mainly European, experience, which, especially in the last decade, demonstrates the weight of the cultural factor in urban development focusing on the economic dimension. In the course of searching the relationship between cultural and economic development, the museums have constituted, and continue to constitute, a particularly interesting research object. Examples of the various concepts and practices that are related with museums are: the construction of the `cultural image' of cities, the quest for cultural identity, the support and promotion of these elements as `goods' in the external environment of cities, and the combination of tourist resources. The examination of the international experience constitutes the basis of the attempt to respond to three fundamental questions: a) in what ways, and with what means, is museum management connected with the effective promotion and support of the `cultural image' of the cities', b) in what ways is the effective promotion and support of the `cultural image' connected with the creation of a competitive advantage for the particular city and its sustainable economic development, and c) does the `selling of cultural identity' of the cities constitute an imperative need or a necessary evil that the cities cannot avoid in both cases' In order to respond to the above questions strategically planned methodologies, ways and means are described and analysed: strategic planning, management, empirical research, segmentation of potential markets-targets, configuration of `cultural tourist packages', place marketing. Particular attention is paid to the role of museums in the urban tourism development process, since tourism constitutes one of the strongest productivity factors in many European cities. The main hypotheses that are going to be tested are the enforcement by the tools of planning and management of the conditions of sustainability and competitiveness, and the contribution of their use to the increasing role of museums in the cultural and economic development of cities. The paper concludes with proposals referring to the case of Greece. In order to examine the role and the importance of museums in the economic and historic development of Greek cities, a threefold structure is followed: framework analysis (i.e. examination of the main weaknesses in the internal environment of museums, identification of the image and administration of museums etc.), secondary data analysis (regional distribution of number and visitors of museums) and presentation of the main research methodology (combination of questionnaires, interviews and statistical data) of an empirical research. The main contradiction is that, while historicity and cultural heritage constitute factors that traditionally characterize Greece, the ways and means with which this factors can constitute dynamic levers of economic development refer to a new reality and new conditions of development which, till the present, have not been taken into serious consideration.
Keywords: 330